2009
DOI: 10.1111/j.1741-3737.2009.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Parenting and Adolescents' Sexual Initiation

Abstract: This study draws on social control and social learning theories to examine the role of datingspecific attitudes and practices as predictors of adolescents' sexual initiation. We include attention to the adolescent's reaction to control attempts as a further means of assessing family dynamics (i.e., frequency of dating disagreements). The study uses longitudinal data from 697 adolescents who were not sexually active at the first interview as well as separate interviews with parents. In models that include all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 23 publications
3
58
0
6
Order By: Relevance
“…In line with research evidences elsewhere and diverging from the Zambian study the findings of this study shown that parent child connectedness is protective against risky sexual behavior [20][21][22][23][24][25][26]. This difference could be explained by cultural differences.…”
Section: Discussionsupporting
confidence: 88%
“…In line with research evidences elsewhere and diverging from the Zambian study the findings of this study shown that parent child connectedness is protective against risky sexual behavior [20][21][22][23][24][25][26]. This difference could be explained by cultural differences.…”
Section: Discussionsupporting
confidence: 88%
“…This is in tandem with the assertions of Miller [15] that "caregiver warmth and related constructs may protect against early sexual initiation and the potential consequences of sex during adolescence. More so, data from both American and European youth suggest that care giver caring, caregiver involvement are inversely associated with sexual initiation in adolescence [16]. Transitional Teens Model also identified parental influence as one of the key element that significantly affects and influence adolescence behaviours.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Esta função pode ser especialmente difícil para os pais 'latinos', pois eles podem ter dificuldades em ensinar os valores tradicionais de sua cultura para seus filhos enquanto as crianças se tornam mais aculturadas na sociedade americana (BARKLEY & MOSHR, 1995;ESPIN, 1984). Os pais podem tentar adiar os comportamentos de namoro de seus filhos através do controle parental, como quando dão ou não permissão para começar a namorar (LONGMORE et al, 2009 GUILAMO-RAMOS et al, 2005;ANESHENSEL, FIELDER & BECERRA, 1989;FLORES et al, 1998;FORD & NORRIS, 1993). No entanto, a maioria das pesquisas que trataram sobre a juventude e início da vida adulta 'latina' usam o termo 'latino' como um hiperônimo que inclui imigrantes de mais de 20 países diferentes (DRISCOLL et al;.…”
Section: Influência Dos Paisunclassified
“…Isto está de acordo com as pesquisa anteriores, que encontraram uma diferença de gênero nos comportamentos de namoro dos jovens 'latinos', com os rapazes tendo estes comportamentos em uma idade mais precoce que as meninas (DRISCOLL et al, 2001;RAFFAELLI, 2005 (DORN-BUSCH et al, 1985;HOGAN & KITAGAWA, 1985;MILLER, MCCOY, OLSON & WALLACE, 1986). Em sua maioria, os pais da América Central foram bem sucedidos em postergar o início dos comportamentos de namoro, bem como da vida sexual, de seus filhos, ao exercerem o controle parental sobre eles (LONGMORE et al, 2009). Mais especificamente, eles foram bem sucedidos em limitar as escolhas dos adolescentes sobre relacionamentos íntimos (LONGMORE et al,2009).…”
Section: Primeiro Encontrounclassified